PENGEMBANGAN STRATEGI E-MARKETING UMKM DI INDONESIA - Dihin Septyato; Ignatius Joko Dewanto (UPT Penerbitan Universitas Jember)
Research objective is to produce a model of e-Marketing strategies of MSMEs in Indonesia. The development of the Internet improvethe way of doing business from traditional to electronic, no denying that the economic activity leading to the marketing of electronic. MSMEs are the spearhead of Indonesian entrepreneurs need some improvement, especially in strategic planning, marketing and e-marketing. The research methodology used is: SWOT analysis, marketing survey, e-marketing survey and e-marketing strategy planning. Results of the research is to produce a design strategy e-marketing MSMEs in Indonesia, and the sustainability of this research is to build a portal e-marketing MSMEs with methods Software Development Life Cycle (SDLC) and Object Analysis Application Development (OOAD) and further to facilitate MSMEs in increasing sales and eventually can strengthen the macro economy in Indonesia as a whole.